Impact of agronomic practices on microbial diversity in brown-desert soil: insights from the Aksu region, Xinjiang - Wenbo Guo; Yanbo Fu; Silayiding Simayi; Yunmeng Wen; Qingyong Bian; Jinquan Zhu; Zhigang Liu; Hanming Su; Yanhong Wei; Guohong Liu; Haifeng Li (Frontiers in Microbiology)
This study highlights how different agronomic practices reshape the microbial communities structure in brown-desert soils of Xinjiang’s Aksu region, with the goal of informing sustainable soil stewardship and agricultural strategies. Employing an L9 (34) orthogonal array, we assessed the effects of different planting densities, irrigation levels, and fertilization strategies on the soil’s physicochemical properties, enzymatic activity, and microbial community composition. Our results highlight the dual role of fertilization: while it is the best strategy to increase agricultural productivity on low-fertility soils in the short term, excessive fertilization can have potentially detrimental effects. (1) it triggers salt accumulation and exacerbates salinization, and (2) it leads to an imbalance in C/N metabolism that inhibits microbial bioactivity. Through high-throughput sequencing, we identified significant shifts in the soil’s bacterial and fungal populations (e.g., Proteobacteria and Ascomycota) in response to agricultural interventions, with the type and extent of fertilization being pivotal to microbial diversity. Redundancy analysis revealed a significant interplay between soil microbial assemblages and underlying physicochemical attributes. This research underscores the necessity for judicious agronomic practices to maintain the delicate balance of microbial life within the soil, offering critical insights for the sustainable soil management of agricultural lands in Xinjiang.